EMPYAK RAGUMAN, TRADISI DAN ESTETIKA RUMAH TRADISIONAL JAWA YANG SEMAKIN MEMUDAR - Vitasurya, Vincentia Reni; Hadi, Purwanto (Universitas Atma Jaya Yogyakarta, 2019)
Abstract: Traditional Javanese houses known for their rich traditions are symbolized by the use of ornaments, construction and building materials. Empty raguman is one of the architectural elements of a Javanese house, in the form of an inner roof coating that functions as a ceiling. The sweetness made of bamboo blades arranged in a certain pattern is a symbol of the level of socio-economic ability of the homeowner. Its existence functions aesthetically and describes a strong tradition. The tradition of making empyak began with processing bamboo, assembling and installing fish is a manifestation of the value of mutual cooperation in Javanese society in the past. At present, empyak raguman is rarely found in traditional Javanese houses built in the modern era. The loss of this element is due to changes in the lifestyle of traditional communities in urban and rural areas. This paper aims to review the beauty of tradition, tradition and aesthetics in Javanese homes. The method used is literature review and its comparison with the practice of implementing it in some cases of traditional houses. The tradition of putting up a lot of raguman has not been carried out anymore, but the existence of empiri raguman which is still preserved is a symbol of pride for traditional homeowners. The results of this study are one of the inputs to preserve traditional values in Javanese houses.Keywords: empyak raguman, javanese house, traditional architecture, tradition, aestheticsAbstrak: Rumah tradisional Jawa dikenal kaya tradisi yang disimbolkan melalui penggunaan ornamen, konstruksi dan bahan bangunan. Empyak raguman adalah salah satu elemen arsitektur rumah Jawa, berupa pelapis atap bagian dalam yang berfungsi sebagai langit – langit. Empyak raguman terbuat dari bilah bambu yang disusun dengan pola tertentu menjadi simbol dari tingkatan kemampuan sosial ekonomi pemilik rumah. Keberadaannya berfungsi secara estetika dan menggambarkan tradisi yang kuat. Tradisi pembuatan empyak dimulai dengan pengolahan bambu, merangkai dan memasang empyak merupakan perwujudan nilai gotong royong masyarakat Jawa di masa lalu. Saat ini, empyak raguman jarang ditemukan pada rumah tradisional Jawa yang dibangun pada era modern. Hilangnya elemen ini karena perubahan gaya hidup masyarakat tradisional di perkotaan dan di perdesaan. Tulisan ini bertujuan mengulas kembali empyak raguman, tradisi dan estetikanya dalam rumah Jawa. Metode yang digunakan adalah kajian literatur dan komparasinya dengan praktek pelaksanaannya pada beberapa kasus rumah tradisional. Tradisi memasang empyak raguman sudah tidak dijalankan lagi namun keberadaan empyak raguman yang masih terpelihara menjadi simbol kebanggaan bagi pemilik rumah tradisional. Hasil kajian ini menjadi salah satu masukan untuk melestarikan nilai – nilai tradisional pada rumah Jawa.Kata Kunci: empyak raguman, rumah Jawa, arsitektur tradisional, tradisi, estetika